Confessions of an English opium-eater and other writings - De Quincey, Thomas (London : Penguin Books, 2003)
Confessions is a remarkable account of the pleasures and pains of worshipping at the 'Church of Opium'. Thomas De Quincey consumed daily large quantities of laudanum (at the time a legal painkiller), and this autobiography of addiction hauntingly describes his surreal visions and hallucinatory nocturnal wanderings through London, along with the nightmares, despair and paranoia to which he became prey. The result is a work in which the effects of drugs and the nature of dreams, memory and imagination are seamlessly interwoven. Confessions forged a link between artistic self-expression and addiction, paving the way for later generations of literary drug-users from Baudelaire to Burroughs, and anticipating psychoanalysis with its insights into the subconscious." "This edition is based on the original serial version of 1821, and reproduces the two 'sequels', 'Suspiria de Profundis' (1845) and 'The English Mail-Coach' (1849). It also includes a critical introduction discussing the romantic figure of the addict and the tradition of confessional literature, and an appendix on opium in the nineteenth century.
Keywords: Drug addicts -- Biography. -- Great Britain; Authors, English -- Biography. -- 19th century